Synthetic studies towards the total synthesis of (-)-codonopsinine, an anti-hypertensive compound from codonopsis clematidea / Mohd Fazli Mohammat @ M Yahya - Mohammat @ M Yahya, Mohd Fazli (2010)
In this study (-)-codonopsinine was chosen as the synthetic target molecule due to its unique trans /?e«tasubstituted pyrrolidine structure as well as remarkable antibiotic and hypotensive activity. The synthetic approach towards the total synthesis of codonopsinine requires an appropriate diketo pyrrolidinone ring template, formed by Dieckmann cyclisation of an intermediate diester which provided the p,(3-diketo pyrrolidinone or through condensation with ring closure via multicomponent reactions to yield different (3,y-diketo ring template. Performing series of successive functional groups modification on both ring templates, which include demethoxycarbonylation, keto reduction, O-protection and P-elimination, successfully furnished over 20 pyrrolidine type compounds- in moderate to good yields. In this study, an important intermediate of olefin, 67 was successfully synthesised in 9 steps with an overall yield of 18%. Nevertheless, a different intermediate of acyloins, 82 with completed JV-Me installation in the ring was also achieved in 3 steps (with an overall yield of 18%) via the multicomponent reactions. Biological studies conducted on some of the codonopsinine derivatives confirmed to exhibit from moderate to the most potent activity towards anti-MRSA and efflux pump inhibition. In brief, two novel synthetic approaches towards the total synthesis of codonopsinine were devised which offer interesting new scientific knowledge and findings.